2021
DOI: 10.3390/ma14133506
|View full text |Cite
|
Sign up to set email alerts
|

Organosulfur Materials with High Photo- and Photo-Oxidation Stability: 10-Anthryl Sulfoxides and Sulfones and Their Photophysical Properties Dependent on the Sulfur Oxidation State

Abstract: While few studies show only symmetrical and poorly mono-SOn (n = 0–2) substituted acenes, in this study, we present a synthesis of a new group of unsymmetrical, significantly substituted derivatives, which revealed unique photophysical properties. Both sulfides (S), sulfoxides (SO) and sulfones (SO2) showed very high photochemical stabilities, unusual for these groups, during UV-irradiation at 254/365 nm (air O2 and Ar), which was higher than any found in the literature. For the (S)/(SO) series (254 nm), the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The mixture of alcohol and phosphine in the presence of acid HA spontaneously cyclized to give products 11A-16A (A = anion) due to the presence of the ortho-acetal function, which, under acidic conditions, enabled the Friedel-Crafts (F-C) cyclization. The products were not the expected anthracenes III, as was the case during the previously described intramolecular hetero-Friedel-Crafts-Bradsher reactions [15][16][17], but 9,10-dihydroanthrols with a non-aromatic middle ring containing both 9-hydroxyl and 10-phosphonium groups. The subsequent Bradsher dehydration is usually the next step after the F-C reaction leading to the aromatic system, but not in this case [24].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The mixture of alcohol and phosphine in the presence of acid HA spontaneously cyclized to give products 11A-16A (A = anion) due to the presence of the ortho-acetal function, which, under acidic conditions, enabled the Friedel-Crafts (F-C) cyclization. The products were not the expected anthracenes III, as was the case during the previously described intramolecular hetero-Friedel-Crafts-Bradsher reactions [15][16][17], but 9,10-dihydroanthrols with a non-aromatic middle ring containing both 9-hydroxyl and 10-phosphonium groups. The subsequent Bradsher dehydration is usually the next step after the F-C reaction leading to the aromatic system, but not in this case [24].…”
Section: Resultsmentioning
confidence: 61%
“…Earlier, we elaborated a new approach to mono-hetero (Z = OR, SR)-substituted acenes IV via the hetero-Friedel-Crafts-Bradsher (F-C-B) cyclization of ortho-O,O-acetals, S,S-dithioacetals and O,S-thioacetals II obtained from diarylmethanols I [14][15][16][17]. In this reaction, a new benzene ring, fused to two other (hetero)aromatic moieties, ArI and ArII, is formed to give acenes IV (Scheme 1, path a).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from our preliminary work [ 70 , 71 ], this review showed, practically, a lack of works devoted to the highly substituted acene systems. It is noteworthy that highly substituted acenes containing thioorganic substituents showed extremely high thermal and photochemical stabilities, properties that would be interesting to verify for acenes with organophosphorus substituents [ 101 , 102 ]. Furthermore, the absence of hetero(S, Se)-analogs of phosphonates and phosphates was recorded during the reviewed period, which additionally opens the way for further research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracene and its derivatives are particularly attractive due to high thermal stability [ 3 ], relatively good solubility, low price, blue photoluminescent [ 4 ] and electroluminescent properties [ 5 ]. Many blue-light-emitting materials with an anthracene core structure [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] have been developed; however, deep blue is still in demand due to the lack of electrically and photochemically stable light-emitting materials [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%